Science in today's world : research in daily life 1 - Climente, Richard F.; Julaton, Aaron Bren E.; Orleans, Antriman V. (Quezon City : Sibs Publishing House, Inc., 2016)
"The Science in Today's World for Senior High School Research in Daily Life 1 is written in compliance with the Philippine K to 12 curriculum." It consists of three units. Unit 1 gives an introduction to research. Unit 2 describes a good research problem and identifies ways to look for and formulate. Unit 3 then presents methods to collect, analyze, and interpret relevant data to be able to form conclusions and make recommendations. By working through the book, you will increase your understanding of how qualitative research relates to the world and be in a better position to make informed decisions in daily life."
Includes bibliographical references.
English text.
Keywords: Research -- Methodology